The carbon flux of global rivers: A re-evaluation of amount and spatial patterns. (September 2017) - Li, Mingxu; Peng, Changhui; Wang, Meng; Xue, Wei; Zhang, Kerou; Wang, Kefeng; Shi, Guohua; Zhu, Qiuan
Highlights: An updated riverine carbon flux database including 263 world's largest rivers. Spatial patterns of riverine carbon fluxes varied river basins and related to generating and transfer factors. Global rivers deliver 1.06 Pg C from land to estuary every year in recent years. Abstract: Global rivers connect three large carbon reservoirs in the world: soil, atmosphere, and ocean. The amount and spatial pattern of riverine carbon flux are essential for the global carbon budget but are still not well understood. Therefore, three linear regression models for riverine DOC (dissolved organic carbon), POC (particulate organic carbon), and DIC (dissolved inorganic carbon) fluxes were established with related generating and transfer factors based on an updated global database. The three models then were applied to simulate the spatial distribution of riverine DOC, POC, and DIC fluxes and to estimate the total global riverine carbon flux. The major conclusions of this study are as follows: the correlation analysis showed that riverine DOC flux is significantly related to discharge ( r 2  = 0.93, n = 109) and soil organic carbon amount ( r 2  = 0.60), POC flux increases with discharge ( r 2  = 0.55, n = 98) and amount of soil erosion ( r 2  = 0.48), and DIC flux is strongly linked to CO2 consumption by rock weathering ( r 2  = 0.66, n = 111) and discharge ( r 2  = 0.63). In addition, Asia exports more DOC and POC than other continents and North America exports more DIC. The Atlantic Ocean accepts the major portion of riverine DOC, POC, and DIC fluxes of all the oceans. The highest riverine DOC flux occurs in the 0–30°S zone, and the highest riverine POC and DIC fluxes appear in the 30–60°N zone. Furthermore, re-estimation revealed that global rivers export approximately 1.06 Pg C to oceans every year, including 0.24 Pg DOC, 0.24 Pg POC, 0.41 Pg DIC, and 0.17 Pg PIC.